The adhesive system and root canal region do not influence the degree of conversion of dual resin cement (Journal of Applied Oral Science, 2010)
OBJECTIVES: The aim of this study was to evaluate the influence of two adhesive systems and the post space region on the degree of conversion of dual resin cement and its bond strength to root dentin. MATERIAL AND METHODS: One three-step etch-and-rinse (All-bond 2, Bisco) and another one-step self-etch (Xeno III, Dentsply) adhesive systems were applied on 20 (n=10) crownless bovine incisors, at 12-mm-deep post space preparation, and a fiber post (DT Light Post, Bisco) was cemented using a dual cure resin cement (Duo-Link, Bisco). Three transverse sections (3 mm) were obtained, being one from each study region (cervical, middle and apical). The degree of conversion of the dual cure resin cement was determined by a micro-Raman spectrometer. The data (%) were submitted to repeated-measures analysis of variance and Tukey's test (p